Cause analysis of stamping cracking and concealed cracking of tailgate inner plate. Issue 1 (1st December 2022) - Liu, Xueli; Huang, Geng; Zhu, Haoyu; Li, Liejun
Abstract: With the development of automobiles toward lightweight and comfort, the production of auto parts has higher and higher requirements for stamping materials and parts forming quality. During the stamping and manufacturing process of the passenger car tailgate inner plate, the tailgate inner plate has many cracks, concealed cracks, and other defects. In this paper, the fracture morphology of the defect section was observed, and the composition and mechanical properties were measured. At the same time, the production process of the steel plate and the working condition of the stamping die were analyzed. The results show that the cracking and concealed cracking defects of stamping sheets are mainly caused by the inclusion of die and sheet. Through the adjustment of the plate production process and mold, the cracking and concealed cracking defects disappeared. This work also provides a reference for the solution to stamping cracking defects in the future.